Arabic Learning Based On E-Learning Using Arabic Teacher Website In The Pandemic Era Of Covid-19 - Binti Jasni, Nur Salsabila; Ardiansyah, Ade Arip (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
This study aims to describe the Arabic Teacher's website as e-learning based Arabic language learning during the Covid-19 pandemic. The method used in this research is a descriptive qualitative method. There have been many studies that discuss learning Arabic based on E-Learning. However, it is only limited to one aspect while learning Arabic using the Arabic teacher website covers various skills and theoretical issues. The results showed 1) E-Learning Arabic Teacher is a complete website designed as an advanced learning Arabic during the Covid-19 pandemic; 2) The Arabic learning approach by using the Arabic teacher E-Learning website is based on the same teaching method programmed, develop internet-based independent learning effectively using a purposeful computer so that learners can learn Arabic in a balanced way read, write, listen, and speak. 3) E-Learning Arabic Teacher provides several main menus including; Arabic languages such as reading, stories (basic, intermediate, advanced), grammar (nahwu), structures (sentence patterns), dictation (imla'), songs and games (songs and games), Questionnaires (assessment sheets) accompanied by an electronic book, MP3, and Video.